Legacy Effect of Coronary Perforation Complicating Percutaneous Coronary Intervention for Chronic Total Occlusive Disease: An Analysis of 26 807 Cases From the British Cardiovascular Intervention Society Database. (May 2017) - Kinnaird, Tim; Anderson, Richard; Ossei-Gerning, Nicholas; Cockburn, James; Sirker, Alex; Ludman, Peter; deBelder, Mark; Walsh, Simon; Smith, Elliot; Hanratty, Colm; Spratt, James; Strange, Julian; et al.
Abstract : Background—: Coronary perforation (CP) during chronic total occlusion percutaneous coronary intervention for stable angina (CTO-PCI) is a rare but serious event. The evidence base is limited, and the long-term effects are unclear. Using a national PCI database, the incidence, predictors, and outcomes of CP during CTO-PCI were defined. Methods and Results—: Data analyzed from the British Cardiovascular Intervention Society data set on all CTO-PCI procedures performed in England and Wales between 2006 and 2013. Multivariate logistic regressions and propensity scores were used to identify predictors of CP and its association with outcomes. A total of 376 CP were recorded from 26 807 CTO-PCI interventions (incidence of 1.40%) with an increase in frequency during the study period ( P =0.012). Patient-related factors associated with an increased risk of CP were age and female sex. Procedural factors indicative of complex CTO intervention strongly related to an increased risk of CP with a close relationship between the number of complex strategies used and CP evident ( P =0.008 for trend). Tamponade occurred in 16.6% and emergency surgery in 3.4% of cases. Adverse outcomes were frequent in those patients with perforation including bleeding, transfusion, myocardial infarction, and death. A legacy effect of perforation on mortality was evident, with an odds ratio for 12-month mortality of 1.60 for perforation survivors compared with matched nonperforation survivors without a CP ( P <0.0001). Conclusions—: Many of the factors associated with an increased risk of CP were related to CTO complexity. Perforation was associated with adverse outcomes, with a legacy effect on later mortality after CP also observed. Abstract : Supplemental Digital Content is available in the text.